URBAN RESILIENCE: HOW TO APPLY IN THE PLANNING AND DESIGN PRACTICE? - Novi Maulida Ni'mah; Bakti Setiawan (DIMENSI (Journal of Architecture and Built Environment), 2022)
This paper aims to explore the advocacy of how urban resilience should be put into the discourse of planning and design practice, especially the standing of the concept within planning theory. The study is conducted through a literature review with objectives among others: (1) to get the insight of what is urban resilience concept and how it has been used in the context of the urban and regional system? and (2) to elaborate the potential of urban resilience concept be used in the planning and design practice through the perspective of planning theory. The initial result of the study concludes that the urban resilience concept has the potential to reframe the perspective of planning theory that has been applied nowadays particularly the theory of planning and theory in planning with the emergence of so-called transformative and recovery planning.